ChemInform Abstract: Bad‐Metal‐Layered Sulfide Oxide CsV2S2O. Issue 13 (March 2016) - Valldor, Martin; Merz, Patrick; Prots, Yurii; Schnelle, Walter
Abstract: Polycrystalline powder of the new title compound is prepared by solid state reaction of Cs2 O1.3, VS, S, and V2 O5 (corundum crucible, 700 °C, 40 h).